Cost-Effectiveness Analysis of Oral Antidiabetic Monotherapy with Metformin and Glimepiride in Diabetes Mellitus at Bahteramas Hospital - Pusmarani, Jastria; Apriani, Rini; Himaniarwati, Himaniarwati; Baco, Julianas; Azlimin, Azlimin (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Healthcare expenditure due to diabetes mellitus in Indonesia reaches approximately US143 per person. The largest portion of this cost is attributed to medications. Therefore, ensuring the cost-efficiency and effectiveness of drug use is critically important. This study aims to determine and analyze the cost-effectiveness of antidiabetic drug therapy in patients with type 2 diabetes mellitus in the outpatient department of Bahteramas Hospital in Southeast Sulawesi Province. Descriptive methods and quantitative analysis of medical record data from Type 2 diabetes mellitus (DM) patients and treatment costs at Bahteramas Hospital in 2023. A total of 61 patients were included in the study based on the inclusion criteria. Based on the average cost-effectiveness ratio (ACER), glimepiride was more efficient, with a value of IDR 18,389, compared to metformin, which had an ACER of IDR 25,405. However, based on the incremental cost-effectiveness ratio (ICER), metformin was more cost-effective, with a value of IDR 50,070. While the biguanide group (metformin) appears more cost-effective than the sulfonylurea group (glimepiride) based on ICER, the overall findings indicate that, based on ACER, glimepiride (sulfonylurea) is more cost-effective. Therefore, glimepiride can be recommended as a single oral antidiabetic therapy at Bahteramas Hospital.